Cell membrane-mimicking coating for blood-contacting polyurethanes. (January 2015) - Butruk-Raszeja, Beata; Trzaskowski, Maciej; Ciach, Tomasz
The aim of the present work was to develop simple modification technique for polyurethanes (PUs) intended for use in blood-contacting implants (vascular grafts, heart prosthesis, ventricular assist devices). PU surface was modified with soybean-derived phosphatidylcholine (PC) via one-step dip coating technique. In order to evaluate blood compatibility of the obtained materials, samples were contacted with human blood under static and arterial flow-simulated conditions. The PC-modified surfaces were thoroughly characterized and tested for fibrinogen resistance, the ability to resist platelet adhesion and activation, hemolysis percentage and plasma recalcification time. Results demonstrated significant, more than three-fold reduction in the amount of fibrinogen adsorbed to PC-modified materials as compared to non-modified PU. Analysis of the samples' surface after incubation with blood showed high reduction in platelet adhesion. The results were confirmed by analysis of blood samples collected after shear-stress tests – the percentage of free (non-aggregated) platelets remaining in blood samples contacted with PC-coated materials exceeded 70%. The same parameter measured for non-modified PU was significantly lower and equaled 28%.